Etio-clinical profile and coronary angiographic characteristics of rural patients with acute inferior wall myocardial infarction - Bijay Prakash Yadav; Amitesh Nagarwal; Poonam Kushwaha; Sundeep Mishra; Manna Bhattacharjee (Heart India)
Background: Epidemiological transition is leading to an increased burden of cardiovascular disease among rural populations. Aim: The study evaluated the etio-clinical profile, prevalence, angiographic characteristics, and correlates of inferior wall myocardial infarction (IWMI). Materials and Methods: This was an institution-based, cross-sectional study among 103 consecutive patients. Regression analysis was done to find the correlates of IWMI. Results: The mean age was 59.14 ± 11.65 years. The study consisted of 86.4% males. 86 (83.5%) were smokers and 12 (11.7%) were alcoholics. 30 (29%) were hypertensive and 33 (32%) were diabetic. 41 (39.8%) had a family history of hypertension and an abnormal lipid profile. The mean body mass index was 23.09 ± 3.62 kg/m2. The mean systolic blood pressure and diastolic blood pressure were 127.23 ± 30.71 mmHg and 77.98 ± 15.83 mmHg, respectively. 4 (3.9%) had COVID-19 disease and 102 (99%) were vaccinated for it. The total occlusion of the vessel was found among 71 (68.9%) subjects. Single-vessel disease was the most prevalent condition – 39 (37.9%). Proximal site occlusion was found among 62 (60.2%) of subjects. Sinus bradycardia was present among 44.7% of subjects. Age (adjusted odds ratio [aOR] =0.89, 95% CI: [0.82–0.97]), COVID-19 disease (aOR =0.011, 95% CI: [2.11e–0.58]), history of hypertension (aOR =11.18, 95% CI: [1.25–99.65]), and sinus bradycardia (aOR =10.41, 95% CI: [1.22–88.63]) were significant predictor of inferior wall ST-segment elevation myocardial infarction (IWSTEMI). The most frequent complication was rhythm disturbances. Conclusion: More than four of five were smokers and rhythmic disturbances were present in nearly one-fifth of subjects. Young age, male sex, hypertension, COVID-19 disease, and sinus bradycardia were significant predictors of IWSTEMI.